2007
DOI: 10.1016/j.stam.2007.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of dyes and organic contaminants in water using nanocrystalline anatase and rutile TiO2

Abstract: Nanocrystalline TiO 2 was synthesized by controlled hydrolysis of titanium tetraisopropoxide. The anatase phase was converted to rutile phase by thermal treatment at 1023 K for 11 h. The catalysts were characterized by X-ray diffraction (XRD), diffuse reflectance spectroscopy (DRS), Fourier-transform infrared absorption spectrophotometry (FT-IR) and N 2 adsorption (BET) at 77 K. This study compare the photocatalytic activity of the anatase and rutile phases of nanocrystalline TiO 2 for the degradation of aceto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
132
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(155 citation statements)
references
References 14 publications
5
132
2
Order By: Relevance
“…The titanium dioxide nanoparticles' time-dependent treatment with methyl red dye solution decreases peak intensity was compared with control (methyl red solution) (Sankar et al 2014a). The titanium dioxide nanoparticles act as an excellent photocatalytic agent, due to their strong oxidizing power, non-toxicity and long-term stability (Tayade et al 2007). The size, charge and morphology of synthesized nanoparticles might influence the enriched photocatalytic degradation activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The titanium dioxide nanoparticles' time-dependent treatment with methyl red dye solution decreases peak intensity was compared with control (methyl red solution) (Sankar et al 2014a). The titanium dioxide nanoparticles act as an excellent photocatalytic agent, due to their strong oxidizing power, non-toxicity and long-term stability (Tayade et al 2007). The size, charge and morphology of synthesized nanoparticles might influence the enriched photocatalytic degradation activity.…”
Section: Resultsmentioning
confidence: 99%
“…This SPR arises from the coherent existence of free electrons in the conduction band due to the small particle size. Among abundant metal oxide nanoparticles, semi-conductive titanium dioxide nanoparticles have apprehensive interest due to their distinctive properties and numerous potential technological applications such as ability to decompose chemical compounds, act as a biosensor, photocatalysis, memory devices, solar cell sensors, super hydrophilic and antibacterial properties (Tayade et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…2 Also, the higher number of surface catalytic sites enables less recombination of electron-hole pairs, which is the rate-determining step in the photocatalytic degradation. 36 Again, the sample with the greatest specific surface area was the unchelated one. Therefore, photocatalytic activity is in concordance with bandgap and specific surface area values.…”
Section: Resultsmentioning
confidence: 98%
“…Electron-hole pair generation is dependent on bandgap, 36 influencing the intensity of light that could be absorbed. Therefore, it is expected that the sample with a lower bandgap, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 film of 80% anatase and 20% rutile was prepared through wet chemical method was used for methylene blue degradation (Rosu et al 2009). Nanocrystalline TiO 2 synthesized by hydrothermal treatment using titanium isopropoxide was used to degrade methylene Blue (Tayade et al 2007). There is no much research reported on degradation of methylene blue by green route synthesized nano TiO 2 .…”
Section: Introductionmentioning
confidence: 99%